Increasing Productivity With Life Planner Mobile Application Using Ionic Framework - Ahmad Naquib, Ali (2023)
A mobile application is a sort of software program created to run on a mobile device, such as a smartphone or tablet, and is frequently referred to as simply an app. This project aims on developing a mobile application that can help users in planning their daily task as well as managing their saving. This is regarding the problems that were found which is users is having a hard time remembering their tasks and managing their finance. The objective of this project is to design and develop an app namely Life Planner that include features such as task list, planning tools, financial planning, as well as time management tools. Due to that, Rapid Application Development (RAD) approach was selected and RAD has 4 phases which are requirements planning, user design, construction, and cutover. RAD focus on timely delivery based on user feedback and active user interaction throughout the development process. The result was a mobile application with capabilities including to-do lists, time management tools, expense monitoring, financial planning tools, budgeting tools, and calendars that were able to satisfy with the starting problems that have been found. In conclusion, the project was able to successfully develop a mobile application (Life Planner) that assists user in their daily life and this application also can be improved with a better enhancement. Additionally, RAD model was also successfully implemented as an early prototype was able to be developed and further changes can be done in an early manner.